Pengaruh Reward dan Punishment terhadap Kinerja Karyawan pada PT Wahana Megahputra Makassar - Cindai Sari; Burhanuddin Burhanuddin; Rezky Amalia Hamka; Ikhwan Maulana Haeruddin; Uhud Darmawan Natsir (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2026)
The purpose of this research is to examine how rewards and punishments influence employee performance at PT Wahana Megahputra Makassar, both individually and simultaneously. This study aims to determine the extent to which rewards and punishments can help employees improve their job performance. A quantitative method with an associative approach was applied in this study. The research involved 60 permanent and contract employees of PT Wahana Megahputra Makassar as the population. The population was selected using a saturated sampling technique, also known as a census. Data were collected through questionnaires, observations, and documentation. Multiple linear regression analysis using SPSS version 25 was employed to analyze the data and determine how the independent variables (rewards and punishments) affect the dependent variable (employee performance). The findings indicate that both rewards and punishments have a positive and significant impact on employee performance. The results also show that when a company implements a fair and consistent reward and punishment system, employees tend to be more motivated and responsible in carrying out their duties.